Psychometric properties and clinical utility of spinal health outcome measures in school-based interventions among children and adolescents: a systematic review protocol - Q A Louw; Loveness A Nkhata; Anri Human; Yolandi Brink (BMJ Open)
Introduction Spinal health in children and adolescents has global implications, impacting school attendance, academic performance and physical activity. Effective school-based interventions are essential for promoting spinal health literacy, positive behaviours and academic success.Objectives This review aims to collect data on school-based interventions for spinal health in children and adolescents over the past two decades. It will examine interventions such as education, exercise and appropriate furniture, focusing on outcomes including musculoskeletal pain, posture, sedentary behaviour and academic performance. Additionally, the review will describe the psychometric properties and clinical utility of the outcome measures used in these studies.Methods and analysis The systematic review will adhere to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, employing the PICO framework to define criteria for participants, interventions, comparisons, outcomes and study designs. Only English studies published between 2004 and 2024 will be included. Relevant databases will be searched using specific keywords derived from the PICO framework. The Critical Appraisal Tool and the COSMIN Risk of Bias tool will be used to evaluate the methodological quality and risk of bias in the selected studies. Review authors will independently assess articles, resolving discrepancies through consensus. Statistical analyses will be performed using CADIMA V.2.2.4.2 April 2023.Results Data will be collected based on various outcome measures, evaluated with an approved checklist and presented through descriptive narratives and tables. Findings will be disseminated via conference presentations, Faculty Research Day and publication in reputable journals.Ethics and dissemination The study will adhere to the ethical principles outlined in the Declaration of Helsinki, ensuring a rigorous approach to minimise bias and guarantee valid results. Studies will be selected based on predetermined criteria following a consistent protocol. The findings will be disseminated through presentations and publication in peer-reviewed journals.PROSPERO registration number The systematic review protocol is registered on PROSPERO (registration number CRD42024543258), with a planned date of commencement from August 2024 to November 2024.